Early Cardiac Mitochondrial Molecular and Functional Responses to Acute Anthracycline Treatment in Wistar Rats - Pereira, Gonçalo Castro (2019)
Doxorubicin (DOX) is an anticancer drug widely used to treat human and nonhuman tumors but the late and persistent cardio-toxicity reduces the therapeutic utility of the drug. The full mechanism(s) of DOX-induced acute, subchronic and delayed toxicity, which has a preponderant mitochondrial component, remains unclear; therefore, it is clinically relevant to identify early markers to identify patients who are predisposed to DOX-related cardiovascular toxicity. To address this, Wistar rats (16 weeks old) were treated with a single DOX dose (20 mg/kg, i.p.); then, mRNA, protein levels and functional analysis of mitochondrial endpoints were assessed 24 h later in the heart, liver, and kidney. Using an exploratory data analysis, we observed cardiac-specific alterations after DOX treatment for mitochondrial complexes III, IV, and preferentially for complex I. Conversely, the same analysis revealed complex II alterations are associated with DOX response in the liver and kidney. Interestingly, H2O2 production by the mitochondrial respiratory chain as well as loss of calcium-loading capacity, markers of subchronic toxicity, were not reliable indicators of acute DOX cardiotoxicity in this animal model. By using sequential principal component analysis and feature correlation analysis, we demonstrated for the first time alterations in sets of transcripts and proteins, but not functional measurements, that might serve as potential early acute markers of cardiac-specific mitochondrial toxicity, contributing to explain the trajectory of DOX cardiac toxicity and to develop novel interventions to minimize DOX cardiac liabilities.